Anti-inflammatory potential of λ-carrageenan by inhibition of IL-6 receptor: in silico study. Issue 1 (November 2021) - Padmi, H; Ansori, A N M; Probojati, R T; Murtadlo, A A A; Sunarwidhi, A L; Hernawan, A; Sunarpi, H; Widyastuti, S; Nikmatullah, A; Prasedya, E S
Abstract: In some cases, the immune system in COVID-19 patients leads to the release of excess cytokine production (cytokine storm), which will potentially develop into pneumonia. Interleukin 6 (IL-6) plays the role of pro-inflammatory cytokine, it is a receptor mediated signalling system. Macroalgae is well known as a source of valuable bioactive substances with potential biological activities. Among them is the sulphated polysaccharide lambda-carrageenan λ-CGN which has been reported as an anti-inflammatory agent. However, its mechanism of action against IL-6 production is currently unknown. This study aims to predict potential molecular mechanisms of λ-CGN chemical compound against IL-6 expression through in silico study. Chemical compound of λ-CGN and target protein in this study were obtained from the pubchem and protein data bank (PDB). The molecular docking prediction was conducted with PyRx software, the result is λ-CGN compound showing strong binding energy to bind target protein IL-6 receptor with the value of -5.9 kcal/mol. Based on the results of in silico study, the sulphated polysaccharide λ-CGN potentially inhibits IL-6R expression by binding ligand pocket with six conventional hydrogen bonds (amino acid residus: His256, His 257, Trp 219, Arg 231, and Asp 221) and two carbon hydrogen bonds (amino acid residus: THR 218 and GLN 220). Binding with these amino acid residues potentially contributes to IL-6 receptor structural change which could result in functional change. Hence, further studies related to in vitro and in vivo investigations would be interesting to further understand the inhibitory mechanism of λ-CGN against IL-6.